Investigation of Effect of Slab Opening Location to the Shear Stress - Yon, Burak; Oncu, Mehmet Emin; Ulucan, Zulfu Cinar (Pamukkale Univ, 2010)
In this study, it is investigated the effect of slab opening location in reinforced concrete building to the structural behavior. For investigation of slab irregularity, three multi storey irregular structures that have different slab opening locations in structure plans and one regular structure are designed. Linear dynamic analyses are performed for the structure models using Time History Analysis method. 13 March 1992 Erzincan Earthquake acceleration records are used for these analyses. It is assumed that slabs of selected structures are modeled as elastic diaphragm. SAP2000 Structural Analysis Program is used in the analyses. Values of slab that near space shear stress obtained from dynamic analyses of selected structures are comparatively evaluated. According to analyses results, it is determined that location of slab opening of structures reasonably both affects the behavior of structures and occurs great slab shear stress.
Keywords: Opening in floor; Time history analysis method; Shear stress